The Comprehensive Instructional Language Learning Model: Exploring its Feasibility and Characteristics - Baaqili, Youssef (Journal of English Language Teaching and Applied Linguistics, 2023)
The necessity for a comprehensive theoretical framework is underscored, given that current theories, such as behaviorism, cognitivism, or constructivism, concentrate on distinct facets of language learning. Scholars contend that language learning and teaching necessitate a comprehensive theoretical framework. The theory under consideration is characterized as possessing descriptive, instructional, and evaluative qualities, thereby offering a pragmatic framework for practitioners in English language teaching. This article introduces a comprehensive theoretical framework for language learning that seeks to encompass all the elements inherent in language learning, namely cross-linguistic applicability, psychological adequacy, contextual variables, and a comprehensive and cooperative learning process that is initiated with input, followed by competency building, and ends with engagement. The theory is expounded upon through the utilization of the Evaluative Matrix of a Comprehensive Instructional Language Learning Theory (EMCILLT), which evaluates the various aspects of the teaching-learning experience, utilizing Grice’s maxims (1975) quantity, quality, manner, and relevance. This comprehensive model that encompasses all the aspects of the learning process serves as a basis for comprehending and delineating the intricate nature of language learning. Moreover, it assists teachers in engaging in self-evaluation of their instructional strategies and practices and/or in evaluating methods, approaches, and techniques to enhance the overall teaching-learning experience.